(untitled) (Advancements in Homeopathic Research, 2024)
BACKGROUND-Obesity is one of the greatest public health challenges worldwide. Now a days it is more common in children also. It is not only a medical but also a philosophical, ecological, economic, sociocultural, and psychological problem as well as a severe consequence of our modern value definition to ’receive more and more’. Therefore, physicians are not able to treat obesity broadly and should not be used any tools to achieve certain weight goals. Homoeopathic literatures speak volumes of treatment of such cases.